Chemo-enzymatic synthesis of bicyclic gamma-lactams using clavaminic acid synthase - Baldwin, J; Adlington, R; Bryans, J; Lloyd, MD; Sewell, T; Schofield, C; Baggaley, K; Cassels, R (1997)
Incubation of the γ-lactam analogue of proclavaminic acid, (±)-threo-5-amino-3-hydroxy-2-(1'-aza-2'-oxocyclopentyl) acid, led to production of two bicyclic γ-lactam products.